Can catch share fisheries better track management targets? - Michael C Melnychuk; Timothy E Essington; Trevor A Branch; Selina S Heppell; Olaf P Jensen; Jason S Link; Steven J D Martell; Ana M Parma; John G Pope; Anthony D M Smith (Fish and Fisheries, 2012)
Fisheries management based on catch shares – divisions of annual fleet‐wide quotas among individuals or groups – has been strongly supported for their economic benefits, but biological consequences have not been rigorously quantified. We used a global meta‐analysis of 345 stocks to assess whether fisheries under catch shares were more likely to track management targets set for sustainable harvest than fisheries managed only by fleet‐wide quota caps or effort controls. We examined three ratios: catch‐to‐quota, current exploitation rate to target exploitation rate and current biomass to target biomass. For each, we calculated the mean response, variation around the target and the frequency of undesirable outcomes with respect to these targets. Regional effects were stronger than any other explanatory variable we examined. After accounting for region, we found the effects of catch shares primarily on catch‐to‐quota ratios: these ratios were less variable over time than in other fisheries. Over‐exploitation occurred in only 9% of stocks under catch shares compared to 13% of stocks under fleet‐wide quota caps. Additionally, over‐exploitation occurred in 41% of stocks under effort controls, suggesting a substantial benefit of quota caps alone. In contrast, there was no evidence for a response in the biomass of exploited populations because of either fleet‐wide quota caps or individual catch shares. Thus, for many fisheries, management controls improve under catch shares in terms of reduced variation in catch around quota targets, but ecological benefits in terms of increased biomass may not be realized by catch shares alone.